Досвід упровадження найбільш перспективних хвойних інтродуцентів у регіоні Карпат - Sishchuk, M. M.; Katsulyak, Y. D.; Sishchuk, N. M.; Stambulska, U. Ya. (Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotsky (URIFFM), 2025)
Introduction The introduction of exotic tree species aims to utilize species, their forms, climatic types, and varieties that have undergone preliminary testing under local conditions and demonstrated promise in one or more economically valuable traits, such as resistance to anthropogenic stress, high productivity, wood quality, durability, early and abundant fruiting, phyto-ameliorative capacity, and ornamental value. Forest ecosystems can better adapt to changing environmental conditions and continue to provide ecological, social, and economic functions when high-quality seeds and planting material of promising introduced species are used in reforestation and afforestation. The aim of this study was to assess the current level of coniferous species introduction in the Ukrainian Carpathians, analyze growth characteristics of selected species, and evaluate their potential for practical forestry applications. Materials and Methods The introduction of coniferous species in the Carpathian region was studied using the authors’ original research with previous scientific findings from the Laboratory of Reforestation and Selection of the Ukrainian Research Institute of Mountain Forestry (UkrRIMF). The analysis also incorporated legislative and regulatory frameworks, financial and departmental records, and both the domestic and international experience in plant introduction and its effective application. Results. Experience in artificial reforestation aimed at increasing the productivity of newly established forest plantations in the Carpathians demonstrates the important role of introduced coniferous species, including Pseudotsuga menziesii, grand fir, white fir, balsam fir, European and Japanese larches, Weymouth pine, yellow pine, black pine, as well as Siberian and Korean stone pines. Studies conducted by the Laboratory of Forest Restoration and Selection of UkrRIMF across all forest management department units in the Carpathians indicate that, by 2024, plantations with introduced coniferous species cover 199.7 ha, accounting for an average of 12.0% of forest plantation projects and involving two non-native species for forest plantation. The larges areas of introduced species were recorded in the Ivano-Frankivsk region (120.2 ha; 21.2%), followed by the Zakarpattia region (32.9 ha; 5.5%). Smaller areas were observed in the Chernivtsi (27.1 ha; 10%) and Lviv (19.5 ha; 8.9%) regions. Among the introduced species, European larch (Larix decidua) was the most widespread, covering 109.2 ha in Ivano-Frankivsk, 32.9 ha in Zakarpattia, 24.0 ha in Chernivtsi, and 19.5 ha in Lviv, for a total of 185.6 ha (11.2%). In contrast, Pseudotsuga menziesii occupied only 14.1 ha (0.8%) of the forest plantation area. Conclusions The experience of growing 12 species of five genera of four subfamilies of the Pinaceae in the Ukrainian Carpathians region was considered. In the area, 11 species are introduced: Pinus koraiensis, P. sibirica, P. nigra, P. ponderosa, P. strobus, Picea pungens, Larix kaempferi, Pseudotsuga menziesii, Abies balsamea, A. concolor, A. grandis. Larix decidua is a native species in the Transcarpathian region, and from the Ciskarpattia and further east, an introducer. The introduction of Ps. menziesii, L. decidua and L. kaempferi is at the stage of naturalization. Their fast growth, productivity, early and abundant seed production, resistance to pathogens and phytophagous insects have been confirmed. There are objects of a permanent forest seed base. The introduction of A. balsamea, A. grandis and P. koraiensis is at the stage of adaptation; there are no permanent forest seed base objects. P. strobus is recommended to be used in forest crops on southern slopes (800 m above sea level) up to 10–15%, as well as in recreational and health forests and in horticultural and park management, providing fencing or protection from vertebrate pests with repellents. 2 Tables, 26 Refs.